2001
DOI: 10.1046/j.1365-2044.2001.01708-3.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the intubating and standard laryngeal mask airways for airway management by inexperienced personnel

Abstract: SummaryThis re-survey of neurosurgical centres was conducted to determine whether the publication of management guidelines has resulted in changes in the intensive care management of severely headinjured patients (defined as Glasgow Coma Score , 9) in the UK and Ireland. Results were compared with data collected from a similar survey conducted 2 years earlier. Almost 75% of centres monitor intracranial pressure in the majority of patients and 80% now set a target cerebral perfusion pressure of . 70 mmHg. The u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
5

Year Published

2002
2002
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 20 publications
1
12
0
5
Order By: Relevance
“…However, this technique does not allow the trainee to assess adequacy of ventilation through the device. Insertion of the intubating laryngeal mask airway has been shown to be similarly easy to master with comparable rates of successful insertion by novices [59,60]. Because of the relative ease of learning these techniques, there is little literature on actual methods of training.…”
Section: Live Humansmentioning
confidence: 99%
“…However, this technique does not allow the trainee to assess adequacy of ventilation through the device. Insertion of the intubating laryngeal mask airway has been shown to be similarly easy to master with comparable rates of successful insertion by novices [59,60]. Because of the relative ease of learning these techniques, there is little literature on actual methods of training.…”
Section: Live Humansmentioning
confidence: 99%
“…Previous studies in patients, cadavers and manikin have all proven LMA, FT, LT and Cobra to be efficient tools for airway management in the hands of naïve "intubators" and inexperienced medical personnel [5,6,12-16]. These studies investigated first year medical, paramedical and nursing students, as well as military personnel in combat paramedical or medical education.…”
Section: Discussionmentioning
confidence: 99%
“…[62][63][64] Using cadavers, Choyce et al demonstrated that non-experienced medical students had significantly faster and greater success at ventilation with the use of FT-LMA compared with a C-LMA. 63 Moreover, 67% of these same untrained medical students were able to successfully intubate the trachea through the FT-LMA.…”
Section: Use By Inexperienced Providers and Nonanesthesiologistsmentioning
confidence: 99%